Upaya Peningkatan Potensi Obyek Wisata Unggulan Di Kota Banjarbaru - Wahyu, Tiara (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
Banjarbaru City, Indonesia, holds significant potential in the tourism sector with a variety of attractions. Although some are not widely known, this research focuses on enhancing the potential of key tourist attractions in the city. Supporting and hindering factors for the success of these attractions are identified, including a lack of interest in human resource training, the impact of a hot climate on visitor experiences, limited collaboration with the local community, misunderstandings between managers and the tourism department, insufficient promotion, inadequate facilities and infrastructure, and budget constraints. The study emphasizes that investing in infrastructure maintenance, utilizing cutting-edge technology, intensive promotion, close collaboration with the private sector and local community, effective communication, regular training, and full support from the local government can enhance the prominence of tourist attractions. By addressing these obstacles and implementing the recommended efforts, the development of key tourist attractions in Banjarbaru City is expected to achieve better results.